Alcohol expectancies change in early to middle adolescence as a function of the exposure to parental alcohol use. (1st June 2020) - Smit, Koen; Voogt, Carmen; Otten, Roy; Kleinjan, Marloes; Kuntsche, Emmanuel
Highlights: Alcohol use exposure predicted changes in alcohol expectancies over six months Fathers' and mothers' exposure predicted adolescents' social alcohol expectancies. Fathers' exposure predicted enhancement expectancies of boys. Modeling of alcohol cognitions in adolescence occurs in relatively short periods Abstract: Introduction: The subjective effects of alcohol, i.e., alcohol expectancies (AE), are important predictors of alcohol use. This three-year longitudinal study examined: 1) the development of enhancement, social, coping, and conformity AE from age 10–16; 2) the association between parental alcohol use exposure and positive AE among adolescents and between exposure and changes in AE over the six month period and 3) the moderating effect of gender on the association between exposure and change in AE. Methods: A longitudinal study followed adolescents between 10-13-years old at baseline (N = 755; 45.6 % boys) in six months intervals for three years, resulting in seven measurements. Results: Adolescents most strongly endorsed enhancement AE. Social and coping AE dimensions positively increased over time. The estimated Multilevel Model of Change revealed that exposure to either fathers 'or mothers' alcohol use predicted an increase in social AE six months later (B = .129, SE = .032). Exposure to fathers' drinking predicted an increase in enhancement AE for boys (B = .075, SE = .031) but not for girls (B=-0.045, SE = .030). No associations between parental exposure and other AE dimensions were found. Conclusion: The results add to previous studies in showing that the association between parental drinking behavior and offspring AE develops within short periods. Prevention should, therefore, include explicit guidelines for parents with respect to how their drinking behavior affect their offspring.